Farmers’ willingness to pay for improved forage seed in LIVES Districts of west Shewa Zone, Ethiopia - Gonfa, L. (Haramaya University, 2015)
Higher willingness to pay for improved forage has positive effects on utilization of improved forage which increases livestock productivity. However, the extents to which farmers are WTP for improved forage seed has not been studied at study area. Hence, the objective of this study was to identify determinants of farmers’ WTP for improved forage seed and to assess the seed system in LIVES districts of West Shewa Zone, Ethiopia. The study includes both primary and secondary data. A multi-stage stratified sampling technique was used to collect data from181 farmers. The data were analyzed using descriptive statistics and econometric model. DBDC elicitation format of contingent valuation method was employed to estimate the parameters in the bivariate probit model. From the result of the study: lack of proper linkage between different actors involved in seed systems; inadequate supply of good quality seed at affordable prices; low level of private sector involvement in the formal system were typical challenges in the seed system of the study area. The response of households' for scenario indicated that the mean WTP for alfalfa, elephant grass, oats and vetch was found to be ETB 173.82, 0.54 per cutting, 39.13 and 28.51 per kg, respectively. The results of the model revealed that on-farm income, land holding, total livestock in TLU, access to credit, family size and contact with extension agents had positive and significant effects on WTP. While initial bid prices, off-farm income, distance to all weather roads and input supplier institutions had negative and significant effects on WTP. The study recommended that well coordinated and organized seed systems which comprehend all actors and promising cultivars through well established national extension system should be required in order to fill the current seed system gaps. Moreover, the farmers’ WTP for improved forage should be enhanced by raising farm household asset creation, training and providing credit services.